Impact of Financial Behaviors on the Financial Wellbeing of Vegetable Farmers in Bhaktapur District - Subedi, Dhruba Prasad; Bhandari, Dilli Ram (The Batuk, 2024)
Financial wellbeing is the overall state of an individual's financial health. It reflects the balance between income, expenses, savings, investments, and debt management, ultimately influencing one's financial resilience and quality of life. This study investigates the impact of financial behavior in relation to saving, spending, investment and borrowing on financial wellbeing among vegetable farmers in Bhaktapur District. Required primary data were collected using a structured questionnaire administered through random sampling technique. The respondents comprised 205 vegetables farmers of who produce and sell vegetables in the market. The Smart PLS 4.0 was used to analyze the structural relationships within the proposed theoretical model. The findings validated the set hypotheses that saving behavior, spending behavior, and investment behavior significantly influence financial wellbeing, indicating that prudent financial practices positively contribute to economic stability and growth. However, borrowing behavior does not show a significant effect on financial wellbeing, suggesting that while access to credit may be important, its management and utilization are critical factors to consider for sustainable financial health. Based on the result, policymakers and stakeholders can tailor interventions to enhance financial literacy, improve access to appropriate financial services, and promote sustainable agricultural development in the region. Ultimately, these findings can lead to more informed policies and initiatives aimed at bolstering the financial resilience and livelihoods of vegetable farmers.